2019
DOI: 10.1063/1.5110404
|View full text |Cite
|
Sign up to set email alerts
|

Plastic-crystalline solid-state electrolytes: Ionic conductivity and orientational dynamics in nitrile mixtures

Abstract: Many plastic crystals, molecular solids with long-range, center-of-mass crystalline order but dynamic disorder of the molecular orientations, are known to exhibit exceptionally high ionic conductivity. This makes them promising candidates for applications as solid-state electrolytes, e.g., in batteries. Interestingly, it was found that the mixing of two different plasticcrystalline materials can considerably enhance the ionic dc conductivity, an important benchmark quantity for electrochemical applications. An… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
25
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 69 publications
(154 reference statements)
1
25
1
Order By: Relevance
“…The plasticity state is highly desirable in electrochemical devices as it reduces the problems of poor contact between the electrolyte and the electrode during volume changes. In addition, new studies suggest an enhanced charge transport in PCs doped with ions (Geirhos et al, 2015;Reuter et al, 2019). Nevertheless, to find an explanation of the enhanced conductivity in these systems, thorough investigations on their atomic structure must be carried out.…”
Section: Introductionmentioning
confidence: 99%
“…The plasticity state is highly desirable in electrochemical devices as it reduces the problems of poor contact between the electrolyte and the electrode during volume changes. In addition, new studies suggest an enhanced charge transport in PCs doped with ions (Geirhos et al, 2015;Reuter et al, 2019). Nevertheless, to find an explanation of the enhanced conductivity in these systems, thorough investigations on their atomic structure must be carried out.…”
Section: Introductionmentioning
confidence: 99%
“…The PC electrolytes can be classified into two subgroups: (i) Ionic PCs, 11,12,15,16,17,19,20,22,29 composed of cations and anions, of which at least one is sufficiently complex to allow for orientational degrees of freedom. (ii) Molecular PCs, 13,14,18,30,31,32,33 consisting of neutral molecules and a relatively small amount of admixed salt to provide ionic charge carriers. Obviously, the dynamic rotational disorder in PC electrolytes generates a high-entropy medium, which should be favorable for the translational ion hopping.…”
Section: Introductionmentioning
confidence: 99%
“…Some works assume a direct coupling of the ionic translation dynamics to the rotational motion of the asymmetric ions or molecules via a "paddle-wheel" or "revolving door" mechanism. 10,12,18,32,33,35 Here the ionic conductivity is assumed to be enhanced by transient free volume generated within the lattice by the molecular reorientations. An alternative approach explains the high ionic mobility in PCs based on the peculiar properties of the plastic-crystalline lattice: The weak 2 intermolecular interactions, leading to the high plasticity and orientational disorder in PCs, make them prone to the diffusion of lattice defects and vacancies and/or plane slips.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, it was found that admixing a related molecular species of larger size can considerably enhance the ionic conductivity and the stability range of the plastic phase. 34 NPG and its derivatives have many applications including water based coatings, magnetic coatings, and powder coatings. 31,35 In addition, it is used as an intermediate for the synthesis of lubricants, plasticizers, adhesives, photographic materials, pharmaceuticals, pesticides, fragrances, fabric soeners and vibration dampeners.…”
Section: Introductionmentioning
confidence: 99%